2022
DOI: 10.3390/en15030948
|View full text |Cite
|
Sign up to set email alerts
|

Efficient District Heating in a Decarbonisation Perspective: A Case Study in Italy

Abstract: The European and national regulations in the decarbonisation path towards 2050 promote district heating in achieving the goals of efficiency, energy sustainability, use of renewables, and reduction of fossil fuel use. Improved management and optimisation, use of RES, and waste heat/cold sources decrease the overall demand for primary energy, a condition that is further supported by building renovations and new construction of under (almost) zero energy buildings, with a foreseeable decrease in the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Table 12 shows the results of calculations of pollutant emissions along with the reduction of pollutant emissions after the introduction of the forecast regulation as compared to the period after deep thermal modernization. The calculations were made in accordance with Formulas (10) and (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 12 shows the results of calculations of pollutant emissions along with the reduction of pollutant emissions after the introduction of the forecast regulation as compared to the period after deep thermal modernization. The calculations were made in accordance with Formulas (10) and (12).…”
Section: Resultsmentioning
confidence: 99%
“…The heating load is influenced by several factors, including the building's energy efficiency standard, its heating power and the location of the rooms in relation to each other or to the external walls. Another important aspect is the location of the building in relation to world directions and the density of buildings in the surroundings [11][12][13][14]. Scientific studies have shown that the operating habits and routine of residents with respect to their temperature preferences also have a significant impact on the heat demand [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many modern technologies that will make it possible to provide humanity with nuclear energy and energy from fossil fuels for many years to come. But, despite the world community's attempt to implement a policy of decarbonization of production, the level of atmospheric pollution continues to grow, which leads to the destruction of the biosphere (Ricci et al, 2022). Waste storage, the consequences of accidents, thermal and radiation pollution are also a big problem.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [21] offers legislative steps and highlights significant turning points on the path to a full heat transition in order to accelerate the execution of the roadmap for the decarbonization of the European heating and cooling sector. A case study in Italy concerning the efficient DH in a decarbonization perspective can be found in [22]. To reduce the harmful emissions in DH systems smart technologies can be applied.…”
Section: Introductionmentioning
confidence: 99%